N‐glycosylation of the AMPA‐type glutamate receptor regulates cell surface expression and tetramer formation affecting channel function. Issue 6 (12th November 2018) - Kandel, Munal Babu; Yamamoto, Saki; Midorikawa, Ryosuke; Morise, Jyoji; Wakazono, Yoshihiko; Oka, Shogo; Takamiya, Kogo
Abstract: The AMPA‐type glutamate receptor (AMPA‐R) plays a primary role in principal excitatory synaptic transmission and many neuronal functions including synaptic plasticity that underlie learning and memory. N‐glycosylation is one of the major post‐translational modifications of membrane proteins, but its specific roles in neurons remain largely unknown. AMPA‐R subunits are N‐glycosylated at their extracellular domains during their biosynthesis in the lumen of the endoplasmic reticulum and Golgi system. Six N‐glycosylation sites are presumed to exist in the extracellular domain of GluA1, which is a member of the AMPA‐R subunits. We observed that the intracellular trafficking and cell surface expression were strongly suppressed in the GluA1 mutants lacking N‐glycans at N63/N363 in HEK293T cells. Multimer analysis using Blue Native‐PAGE displayed the impaired tetramer formation in the glycosylation mutants (N63S and N363S), indicating that the mis‐transport was caused by impaired tetramer formation. N63S and N363S mutants were primarily degraded via the lysosomal pathway. Flag‐tagged N363S GluA1, but not N63S GluA1, expressed in primary cortical neuron cultures prepared from GluA1 knockout mice was observed to localize at the cell surface. Co‐expression of GluA2 partially rescued tetramer formation and the cell surface expression of N363S GluA1 but not N63S GluA1, in HEK293T cells. Electrophysiological analysis also demonstrated functional heteromers of N363S GluA1 with GluA2. These data suggest that site‐specific N‐glycans on GluA1 subunit regulates tetramer formation, intracellular trafficking, and cell surface expression of AMPA‐R. Open science badges: This article has received a badge for *Open Materials* because it provided all relevant information to reproduce the study in the manuscript. The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found athttps://cos.io/our-services/open-science-badges/ . Abstract : N‐glycosylation is one of the major post‐translational modifications of membrane proteins, but its specific roles in neurons remain largely unknown. We found that two N‐glycosylation sites in the GluA1 subunit (N63 and N363) are essential for proper tetramer formation and releasing functional AMPARs from the ER to the cell surface. Both glycosylation mutants (N63S and N363S) have short half‐life and quickly undergo degradation via the lysosomal pathway. Additionally, we found that the co‐expression of GluA2 accelerated the tetramer formation and cell surface expression of N363S GluA1. These results added additional evidence for the critical role of N‐glycosylation in AMPA‐R functions. Open Science: This manuscript was awarded with the Open Materials Badge. For more information see:https://cos.io/our-services/open-science-badges/